Ibrahim Al-Wali and his diplomatic role in Yemen 1962-1964 - Jabouri, Rana Abdel Sattar; Abd, Nadia Yassin (Al-Adab Journal, 2023)
The study of personalities is one of the important historical studies because of their active role and great influence in revealing facts and historical events, for several reasons, the most important of which is one of the prominent diplomatic personalities. His philosophy was derived from his studies at the Teachers Institute in Baghdad and then studying sociology and philosophy at the Faculty of Arts, Fouad I University. His personality and his career were smooth and calm, and he did not engage in military adventures and politics. The guardian moved away from partisan work in Iraq and participated in multiple international diplomatic activity the parties.